2011
DOI: 10.7899/1042-5055-25.2.151
|View full text |Cite
|
Sign up to set email alerts
|

Perception of Educational Environment Among Undergraduate Students in a Chiropractic Training Institution

Abstract: Per J. Palmgren, RC, MMedEd, Scandinavian College of Chiropractic, and Madawa Chandratilake, MBBS, MMedEd, University of Dundee Purpose: The impact of the educational environment in student learning is well documented. However, there is a scarcity in the literature exploring the educational environment in chiropractic training institutions. This study aimed to identify the perceived educational environment in a chiropractic training institution and the possible perceptual differences among different demographi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
41
3
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 37 publications
(50 citation statements)
references
References 48 publications
5
41
3
1
Order By: Relevance
“…20,21 DREEM is suitable for gauging the environment in educational contexts, 14 and it has been reported to have good psychometric properties in many diverse contexts, with evidence based on test content (content and construct validity) [22][23][24] and internal consistency (reliability). 19,[25][26][27][28] The instrument has undoubtedly contributed to establishing a greater contextual understanding of professional health care education. Although numerous studies have been carried out to explore medical, osteopathic, dentistry, physiotherapy, and nursing educational environments, there appears to be a gap in the scientific literature on analyses of chiropractic educational environments, with only a few studies endeavoring to identify students' perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…20,21 DREEM is suitable for gauging the environment in educational contexts, 14 and it has been reported to have good psychometric properties in many diverse contexts, with evidence based on test content (content and construct validity) [22][23][24] and internal consistency (reliability). 19,[25][26][27][28] The instrument has undoubtedly contributed to establishing a greater contextual understanding of professional health care education. Although numerous studies have been carried out to explore medical, osteopathic, dentistry, physiotherapy, and nursing educational environments, there appears to be a gap in the scientific literature on analyses of chiropractic educational environments, with only a few studies endeavoring to identify students' perceptions.…”
Section: Introductionmentioning
confidence: 99%
“…We have previously quantitatively introspected both chiropractic and physiotherapy students' perceptions of the educational environment. 4,12,13 These empirical findings suggest that both these groups have similar judgments of the environment and perceive it as very good, but some aspects of the environment recorded low scores in both the cross-sectional and the longitudinal data, such as limited support for stressed students, teachers being authoritarian, and an overemphasis on factual learning. Moreover, even though a handful of surveybased investigations, apart from ours, have been conducted on these student populations, 4,[13][14][15] to our knowledge there are no existing qualitative explorations of how teachers in these contexts experience the educational environment.…”
Section: Introductionmentioning
confidence: 77%
“…Similar results have been reported by Tripathy S et al 1 This view has been reported by other studies as well. 13,14,15,16 Health care system exposed to a diversity of pressures, many of which may cause stress. 13 Guthrie et al 17 reported that even in early years of health care education upto 50% of students' stress is related to aspects of course work.…”
Section: Discussionmentioning
confidence: 99%
“…13,14,15,16 Health care system exposed to a diversity of pressures, many of which may cause stress. 13 Guthrie et al 17 reported that even in early years of health care education upto 50% of students' stress is related to aspects of course work. Bassaw et al 18 have argued that students must be supported all the way through educational path, from entering school to qualifying and beyond.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation